Realtime Student Information Center Application Based on Telegram Bot Case Study at the Faculty of Computer Science, UPN “Veteran” East Java - Rizki Parlika; Arista Pratama (Nusantara Science and Technology Proceedings)
The Faculty of Computer Science, East Java Veterans National Development University as a superior Faculty needs to improve the implementation of Information Technology in carrying out daily Tri Dharma activities. Submission of information quickly to all students is certainly a fundamental requirement. With intermediaries delivering messages such as telegrams, we can provide students with various information related to lectures, guidance, student organizations, etc. in real time and automatically. In general, when students ask through the telegram application, these questions will be answered one by one by a human admin, of course this will be very time-consuming and time consuming. What if this can be done by intelligent robots answering questions from all students according to the topic. Lecturers only fill in various information related to academic information such as guardianship, lectures, guidance on street vendors and Thesis on a web-based application, and students who ask via telegram will get their answers automatically. When students ask via telegram, students will choose a question topic before it cones on a specific topic. If the topic does not exist, the algorithm will try to give the answer that comes closest to the question. Furthermore, when students try to ask questions directly without determining the topic, the algorithm will do a match between the questions with the answer database, then give the closest answer. And also the application which we refer to as BITFIK (Bot of Information based on the Faculty of Computer Science) is also able to save and draw conclusions from various suggestions and input from students regarding the services of Lecturers and Education Personnel in the form of questionnaires. The conclusion can then be seen by the Chairperson through a Web Application built with a combination of the PHP Programming Language and its supporting Variants, the MySQL Server Database, and the Telegram Apps Chatting. Continuous coding and integration will continue to be developed in accordance with FIK's Internal Needs during the Application development period. Based on the explanation above can be formulated as follows "How to build a realtime Student Information Center application based on telegram bot case study at the Faculty of Computer Science, UPN “Veteran” Jawa Timur."